Reactivation of Acute Retinal Necrosis following SARS-CoV-2 Infection - Monica P. Gonzalez; Radames Rios; Mariella Pappaterra; Miguel Hernandez; Allison Toledo; Carmen Santos; Andres Emanuelli; Shree K. Kurup; Armando L. Oliver (Case Reports in Ophthalmological Medicine)
Purpose. To report on a case of reactivation of acute retinal necrosis following SARS-CoV-2 infection. Methods. Observational case report. Observations. A 32-year-old female with a distant history of left retinal detachment secondary to necrotizing herpetic retinitis complained of right-eye vision loss, pain, redness, and photophobia. An ophthalmological examination revealed findings consistent with acute retinal necrosis of the right eye. A polymerase chain reaction (PCR) analysis of the right vitreous was positive for herpes simplex virus type 2 (HSV-2). A coronavirus disease 2019 (COVID-19) screening test using reverse transcriptase- (RT-) PCR was positive for SARS-CoV-2 RNA. Conclusions. Our case suggests that COVID-19 may cause a latent HSV infection to reactivate, causing contralateral involvement in patients with a prior history of HSV-associated acute retinal necrosis.